A microcapsule phase-change energy storage magnesium salt and its preparation method and application

By mixing emulsifier, ultrafine magnesium hydroxide and flexible phase change material to prepare microcapsule phase change energy storage magnesium salts, and applied to SEBS composite materials, the existing materials have poor energy storage effect and low thermal conductivity and flame retardant performance, achieving high-efficiency energy storage, rapid thermal conductivity and multiple flame retardant effects, reducing costs.

CN115873563BActive Publication Date: 2025-03-18JIANGXI HONGYI POLYMERIC MATERIALS +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211662657.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-23
Publication Date
2025-03-18
Estimated Expiration
2042-12-23

AI Technical Summary

Technical Problem

The existing microcapsule phase change energy storage materials have poor energy storage effects, low thermal conductivity and flame retardant properties, and high cost.

Method used

The emulsifier, ultrafine magnesium hydroxide and flexible phase change material are mixed and reacted, and the microcapsule phase change energy storage magnesium salt is obtained after post-treatment, and it is applied to the SEBS composite material.

Benefits of technology

It realizes efficient phase change energy storage, rapid thermal conductivity, and various flame retardant effects, reducing production and use costs and improving the comprehensive performance of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115873563B_ABST
    Figure CN115873563B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of functional material application, and discloses a microcapsule phase-change energy storage magnesium salt and its preparation method and application. The present invention provides a microcapsule phase-change energy storage magnesium salt, which combines ultrafine magnesium hydroxide and flexible phase-change materials together through microencapsulation technology, making full use of the excellent smoke suppression and flame retardant properties of ultrafine magnesium hydroxide, as well as good thermal conductivity properties, including the excellent energy storage properties of flexible phase-change materials, which can not only effectively realize the basic needs of phase-change energy storage, but also can quickly export heat to prevent local heat accumulation, and can also achieve a variety of flame retardant effects in the condensed phase and gas phase, realizing the multiple needs of current energy devices. The preparation process of the present invention is simple, the raw material source is wide and cheap, the production and use costs are low, no large amount of chemical reagents are required, the process is green and pollution-free, and it is suitable for large-scale promotion and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional material application, and in particular to a microcapsule phase-change energy storage magnesium salt and a preparation method and application thereof. Background Art

[0002] At present, the world's energy structure is facing a profound transformation, a new round of energy transformation market is booming, and the growth rate of related products in the energy field is on the eve of an explosion. Based on this, my country has been promoting the development and construction of the energy industry for many years. The low-carbon energy structure and the safe and efficient energy system have become the key core support for promoting energy transformation. Among them, in order to make up for the time difference, intermittency, instability and other defects between energy supply and demand, and further improve the efficiency of energy utilization, thermal energy storage technology has become one of the core technologies to solve the above problems. The widespread application of such materials can not only alleviate the problem of supply and demand differences in time and space, but also improve the problem of overheating and failure of energy electronic devices through passive thermal management. It plays a vital role in improving energy utilization and maintaining the stability of the energy system. Based on the simple and efficient application mode of phase change material thermal management, the preparation of high-value-added phase change functional materials through low-cost raw materials has become one of the important technical supports in thermal management in the tide of energy transformation. Microcapsule phase change materials can encapsulate micro-nano functional materials, absorb and release energy through the change of the material form of the core, and fully realize the goal of efficient thermal management. Considering the sealing, mechanical strength, and performance stability of microcapsule wall materials, among the three types of materials, namely organic wall materials, inorganic wall materials, and organic-inorganic composite wall materials, inorganic wall materials have natural advantages in terms of thermal stability, mechanical strength, and high structural stability, and they have excellent advantages in terms of cost performance that are difficult to surpass in the other two types of wall materials. In recent years, with the increasing demand for energy thermal management materials, the performance requirements for them have also become increasingly higher. In addition to quickly and timely exporting the heat generated by energy components, they must also have higher thermal conductivity and flame retardancy. From this perspective, inorganic wall materials have more inherent advantages than the other two types of wall materials, and the key is that the cost is controllable.

[0003] However, the thermal conductivity of magnesium hydroxide (MH) is lower than that of magnesium oxide, so in the prior art, magnesium hydroxide (MH) cannot be used in existing high-standard energy thermal management devices, and based on the high requirements of energy thermal management devices in phase change energy storage, thermal conductivity, flame retardancy, etc., there are no reports on the application of microcapsule ultrafine hybrid magnesium hydroxide (MH) inorganic functional powder. Therefore, microcapsule ultrafine hybrid magnesium hydroxide (MH) inorganic functional powder is worthy of in-depth study. Summary of the invention

[0004] The purpose of the present invention is to provide a microcapsule phase change energy storage magnesium salt and its preparation method and application, so as to solve the problems of poor energy storage effect, low thermal conductivity and flame retardancy, and high cost of existing microcapsule phase change energy storage materials.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The present invention provides a method for preparing a microcapsule phase-change energy storage magnesium salt, comprising the following steps:

[0007] The emulsifier, ultrafine magnesium hydroxide and flexible phase change material are mixed and reacted, and then post-processed to obtain microcapsule phase change energy storage magnesium salt.

[0008] Preferably, the emulsifier is an aqueous solution of one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, trimethoxysilane, tetraethyl orthosilicate, sodium oleate, sodium rosin acid, sodium laurate, sodium cyclopentaneate, sodium didodecylphenyl ether disulfonate, sodium dibutylnaphthalene sulfonate, sodium methylene diisopropylnaphthalene sulfonate, potassium methylene diisopropylnaphthalene sulfonate and lignin sulfonate; the mass concentration of the emulsifier is 0.1-10wt%; the flexible phase change material is one or more of paraffin, fatty acid and polyol.

[0009] Preferably, the median particle size of the ultrafine magnesium hydroxide is 0.9-1.5 μm; the molar ratio of the emulsifier to the ultrafine magnesium hydroxide is 0.05-10:1; and the molar ratio of the flexible phase change material to the ultrafine magnesium hydroxide is 0.5-5:1.

[0010] Preferably, the temperature of the mixed reaction is 30 to 90° C., and the time of the mixed reaction is 1 to 48 hours.

[0011] Preferably, the mixing reaction is carried out under stirring conditions at a rate of 100 to 2000 r / min.

[0012] Preferably, the specific steps of mixing the emulsifier, ultrafine magnesium hydroxide and the flexible phase change material are: mixing the emulsifier and the flexible phase change material, and then adding the ultrafine magnesium hydroxide for mixing reaction.

[0013] Preferably, the mixing is stirring mixing, the mixing time is 10 to 120 minutes, the mixing temperature is 30 to 80° C., and the stirring rate of the mixing is 100 to 1000 r / min.

[0014] Preferably, the post-treatment is to centrifuge, wash and freeze-dry the product obtained from the mixed reaction in sequence; the centrifugal rate is 1000-9000 r / min, and the centrifugal time is 5-80 min; the reagent used for washing is water, and the number of washings is 2-3 times; the freeze-drying temperature is -80--10°C, and the freeze-drying time is 1-48 h.

[0015] The present invention also provides a microcapsule phase-change energy-storage magnesium salt prepared by the preparation method of the microcapsule phase-change energy-storage magnesium salt.

[0016] The present invention also provides application of the microcapsule phase-change energy storage magnesium salt in a SEBS composite material for general energy thermal management devices.

[0017] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The present invention skillfully combines ultrafine magnesium hydroxide and flexible phase change materials through microencapsulation technology, making full use of the excellent smoke suppression and flame retardant properties of ultrafine magnesium hydroxide, as well as good thermal conductivity, including the excellent energy storage properties of flexible phase change materials, which can not only effectively meet the basic needs of phase change energy storage, but also quickly export heat to prevent local heat accumulation, and also achieve a variety of flame retardant effects in the condensed phase and gas phase, meeting the multiple needs of current energy devices, greatly improving the application value of ultrafine magnesium hydroxide, and promoting its high value in the energy field;

[0019] (2) The preparation process of the present invention is simple and easy, the raw materials are widely available and cheap, and the production and use costs are low. In particular, the ultrafine magnesium hydroxide used in the present invention is prepared by physical methods, which fully avoids the complicated chemical preparation process, and the preparation cost is low, does not require the consumption of a large amount of chemical reagents, and the process is green and pollution-free;

[0020] (3) The present invention prepares a SEBS composite material by adding the prepared microcapsule phase change energy storage magnesium salt to a SEBS matrix. The obtained SEBS composite material has a more delicate surface morphology, controllable surface brightness haze, better mechanical properties, better matrix loading rate and better extrusion stability compared to traditional PVC-based energy materials, and can be repeatedly processed and formed with the help of traditional plastic processing lines. On the premise of achieving the basic goal of energy storage, it ensures halogen-free and environmental protection, and achieves a good balance between mechanical properties and flame retardant properties. The prepared microcapsule phase change energy storage magnesium salt has an appearance of white or off-white, is friendly to the apparent color of the SEBS device matrix, and is conducive to subsequent coloring. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0022] Figure 1 This is a transmission electron microscope image of the microcapsule phase-change energy storage magnesium salt prepared in Example 1;

[0023] Figure 2 This is the particle size distribution diagram of the microcapsule phase-change energy storage magnesium salt prepared in Example 1. DETAILED DESCRIPTION

[0024] The present invention provides a method for preparing a microcapsule phase-change energy storage magnesium salt, comprising the following steps:

[0025] The emulsifier, ultrafine magnesium hydroxide and flexible phase change material are mixed and reacted, and then post-processed to obtain microcapsule phase change energy storage magnesium salt.

[0026] In the present invention, the emulsifier is preferably an aqueous solution of one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, trimethoxysilane, tetraethyl orthosilicate, sodium oleate, sodium rosinate, sodium laurate, sodium cyclopentaneate, sodium didodecylphenyl ether disulfonate, sodium dibutylnaphthalene sulfonate, sodium methylene diisopropylnaphthalene sulfonate, potassium methylene diisopropylnaphthalene sulfonate and lignin sulfonate, and more preferably an aqueous solution of one or more of sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, sodium didodecylphenyl ether disulfonate and potassium methylene diisopropylnaphthalene sulfonate; the mass concentration of the emulsifier is preferably 0.1-10wt%, and more preferably 1-8wt%.

[0027] In the present invention, the flexible phase change material is preferably one or more of paraffin, fatty acid and polyol, and is further preferably paraffin and / or fatty acid;

[0028] The paraffin wax preferably has a carbon number of 14 to 34 and a general structural formula of C n H 2n+2 Saturated hydrocarbons, preferably saturated hydrocarbons having 20 to 30 carbon atoms, are of the general formula C n H 2n+2The fatty acid is preferably one or more of acetic acid, polyvinyl alcohol-600, lauric acid, tristearin, myristic acid, palmitic acid, stearic acid, acetamide and dimethyl fumarate, and more preferably one or more of acetic acid, polyvinyl alcohol-600, tristearin, palmitic acid and acetamide; the polyol is preferably one or more of pentaerythritol, neopentyl glycol and trimethylolaminomethane, and more preferably pentaerythritol and / or neopentyl glycol;

[0029] When the flexible phase change material is paraffin, the flexible phase change material is heated to a clear liquid state and then mixed with an emulsifier and ultrafine magnesium hydroxide for reaction; when the flexible phase change material is fatty acid, the flexible phase change material is heated to a liquid state and then mixed with an emulsifier and ultrafine magnesium hydroxide for reaction; when the flexible phase change material is a polyol, the flexible phase change material is directly mixed with an emulsifier and ultrafine magnesium hydroxide for reaction.

[0030] In the present invention, the oil absorption value of the ultrafine magnesium hydroxide is significantly improved compared with the traditional magnesium hydroxide powder, so that its dispersibility in the polymer material is also improved to a certain extent, and it is helpful to reduce the consumption of resin in the processing process, thereby effectively saving the processing cost; at the same time, the ultrafine magnesium hydroxide as an inorganic wall material can effectively prevent the leakage of the flexible phase change material, has great advantages in thermal conductivity and mechanical strength, and can effectively reduce the application cost and improve the comprehensive performance of the device.

[0031] In the present invention, the ultrafine magnesium hydroxide is obtained by pulverizing, and the median particle size of the ultrafine magnesium hydroxide is preferably 0.9-1.5 μm, and more preferably 1-1.4 μm; the molar ratio of the emulsifier to the ultrafine magnesium hydroxide is preferably 0.05-10:1, and more preferably 0.08-9:1; the molar ratio of the flexible phase change material to the ultrafine magnesium hydroxide is preferably 0.5-5:1, and more preferably 1-4:1.

[0032] In the present invention, the molar ratio of the flexible phase change material core and the ultrafine magnesium hydroxide wall material is crucial to the final melting enthalpy and encapsulation rate of the microcapsule phase change energy storage magnesium salt. Among them, the flexible phase change material core mainly contributes to the phase change latent heat of the phase change material, and the ultrafine magnesium hydroxide wall material plays the role of sealing, enhancing heat conduction, and flame retardancy. The final performance of the microcapsule phase change energy storage magnesium salt directly depends on the content of the coated core material and the external wall material.

[0033] In the present invention, the temperature of the mixing reaction is preferably 30 to 90° C., more preferably 40 to 80° C.; the time of the mixing reaction is preferably 1 to 48 hours, more preferably 2 to 45 hours.

[0034] In the present invention, the mixing reaction is carried out under stirring conditions, and the stirring rate is preferably 100 to 2000 r / min, and more preferably 200 to 1800 r / min.

[0035] In the present invention, the specific steps of mixing the emulsifier, ultrafine magnesium hydroxide and the flexible phase change material are: mixing the emulsifier and the flexible phase change material, and then adding the ultrafine magnesium hydroxide for mixing reaction.

[0036] In the present invention, the mixing is preferably stirring mixing; the mixing time is preferably 10 to 120 min, more preferably 30 to 100 min; the mixing temperature is preferably 30 to 80° C., more preferably 40 to 70° C.; the mixing stirring rate is preferably 100 to 1000 r / min, more preferably 300 to 600 r / min.

[0037] In the present invention, the post-treatment is to centrifuge, wash and freeze-dry the product obtained from the mixed reaction in sequence;

[0038] The centrifugal speed is preferably 1000-9000 r / min, more preferably 2000-8000 r / min; the centrifugal time is preferably 5-80 min, more preferably 10-70 min;

[0039] The reagent used for the washing is preferably water; the number of washings is preferably 2 to 3 times, more preferably 3 times;

[0040] The freeze drying temperature is preferably -80 to -10°C, more preferably -70 to -20°C; the freeze drying time is preferably 1 to 48 hours, more preferably 2 to 45 hours; before the freeze drying, the washed product is dispersed in water; the amount of water used is preferably 1 to 10 wt% of the mass of the washed product, more preferably 2 to 5 wt%; the freeze drying mainly comprises mixing the microcapsule phase change magnesium salt powder obtained by centrifugation and washing with water, placing the mixture in a freeze dryer for low-temperature freezing, and performing solid-state sublimation at low temperature to obtain the final microcapsule phase change energy storage magnesium salt.

[0041] In the present invention, the specific step of mixing the emulsifier and the flexible phase change material is: dropping the emulsifier into the flexible phase change material; the dropping speed is preferably 0.005-0.05 mL / s, and more preferably 0.01-0.04 mL / s.

[0042] The present invention also provides a microcapsule phase-change energy-storage magnesium salt prepared by the preparation method of the microcapsule phase-change energy-storage magnesium salt.

[0043] In the present invention, the microcapsule phase-change energy storage magnesium salt is a white or off-white powder.

[0044] The present invention also provides application of the microcapsule phase-change energy storage magnesium salt in a SEBS composite material for general energy thermal management devices.

[0045] In the present invention, the SEBS composite material comprises the following raw materials in parts by weight: 20-40 parts of SEBS, 1-15 parts of polypropylene, 5-40 parts of microcapsule phase-change energy storage magnesium salt, and 10-30 parts of additives.

[0046] In the present invention, the amount of SEBS is preferably 25 to 35 parts, more preferably 30 to 32 parts; the amount of polypropylene is preferably 2 to 13 parts, more preferably 5 to 12 parts; the amount of microcapsule phase change energy storage magnesium salt is preferably 10 to 35 parts, more preferably 15 to 30 parts; the amount of the auxiliary agent is preferably 15 to 28 parts, more preferably 20 to 25 parts.

[0047] In the present invention, the ultrafine magnesium hydroxide in the microcapsule phase-change energy storage magnesium salt can not only meet the needs of filler, but also can be used as a flame retardant in energy thermal management devices. It can release a large amount of water vapor to dilute the pyrolysis product fragments during the combustion process, and the MgO produced in the condensed phase can adhere to the combustion front to form a strong thermal barrier layer, thereby enhancing the flame retardant properties of the combustion front.

[0048] In the present invention, the SEBS is KRATON SEBSG-1650, KRATON SEBSG-1654, SEBS-6150, YH-502 thermoplastic SEBS, CalpreneH6120, SeptonS-8004, Ningbo Oruit 7332, Japan Asahi Kasei Tuftec SEBSSH1077, Japan Asahi Kasei Tuftec SEBSSH1053, TSRC SEBS-6153, TSRC SEBS-6154, TSRC SEBS-6151, TSRC SEBS-6159, KRATON A1536S EBS, one or more of Sinopec Baling YH-604SEBS and SEBS Li Changrong LCY-9550, further preferably one or more of Kraton (KRATON) SEBSG-1650, Kraton (KRATON) SEBSG-1654, SEBS-6150, CalpreneH6120, SeptonS-8004, Ningbo Oruit 7332, TSRC SEBS-6154, TSRC SEBS-6151, Kraton (KRATON) A1536SEBS, Sinopec Baling YH-604SEBS and SEBS Li Changrong LCY-9550.

[0049] In the present invention, the polypropylene is preferably polypropylene T30S, polypropylene PPH-T-022, polypropylene Yanshan Petrochemical 2401, polypropylene Yanshan Petrochemical S1003, polypropylene Z30S, polypropylene Yanshan Petrochemical 1947, polypropylene Yanshan Petrochemical K7726, polypropylene Yanshan Petrochemical K9935, polypropylene Yanshan Petrochemical K9920, polypropylene Yanshan Petrochemical 1700, polypropylene Yanshan Petrochemical 1828, SK370Y high-transparency polypropylene, polypropylene 6019, polypropylene K8009, polypropylene 5090T, polypropylene 5018T, polypropylene 5350T, One or more of polypropylene T300, polypropylene F280, F350 polypropylene, polypropylene T350 and polypropylene Y2000, further preferably one or more of polypropylene T30S, polypropylene Yanshan Petrochemical S1003, polypropylene Z30S, polypropylene Yanshan Petrochemical K7726, polypropylene Yanshan Petrochemical K9920, polypropylene Yanshan Petrochemical 1700, polypropylene Yanshan Petrochemical 1828, polypropylene 6019, polypropylene 5090T, polypropylene 5018T, polypropylene 5350T, polypropylene F280, F350 polypropylene and polypropylene Y2000.

[0050] In the present invention, the auxiliary agent is preferably one or more of a plasticizer, a composite antioxidant, a lubricant, a toughening agent and white oil, and is further preferably a plasticizer, a composite antioxidant, a lubricant, a toughening agent and white oil;

[0051] The plasticizer is preferably one or more of diisobutyl phthalate, di(2-ethylhexyl) phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate, dimethyl phthalate and diisononyl phthalate, and more preferably one or more of di(2-ethylhexyl) phthalate, dibutyl phthalate, dioctyl phthalate, butyl benzyl phthalate and diisononyl phthalate;

[0052] The composite antioxidant is preferably one or more of hindered phenol antioxidants, phosphite antioxidants and hindered amine antioxidants, and is further preferably hindered phenol antioxidants and phosphites; the hindered phenol antioxidant is preferably one or more of hindered phenol antioxidant 1010, hindered phenol antioxidant 1098 and hindered phenol antioxidant 1024, and is further preferably hindered phenol antioxidant 1010; the hindered amine antioxidant is preferably one or more of light stabilizer Tinuvin770 / DF, light stabilizer Chimassord944FDL, hindered amine light stabilizer HS-944, light stabilizer GW-480, hindered amine light stabilizer HS-508 and light stabilizer Tinuvin292, and is further preferably light stabilizer Chimassord944FDL;

[0053] The lubricant is preferably one or more of calcium stearate, oxidized polyethylene wax, glyceryl stearate, paraffin stearamide and zinc stearate, and more preferably calcium stearate and zinc stearate;

[0054] The toughening agent is preferably one or more of EPDM, ethylene-octene copolymer, ethylene-butene copolymer, acrylonitrile-butadiene-styrene copolymer and styrene-butadiene thermoplastic elastomer, and is further preferably acrylonitrile-butadiene-styrene copolymer and / or ethylene-octene copolymer;

[0055] The white oil is preferably one or more of 26# white oil, 500N white oil, 46# white oil and KN4008 white oil, and more preferably 26# white oil and / or 46# white oil.

[0056] In the present invention, the preparation method of the SEBS composite material comprises the following steps:

[0057] The SEBS and white oil are mixed, and then the other raw materials are added and mixed, and then extruded and granulated, and the SEBS composite material is obtained through molding.

[0058] In the present invention, the mixing is stirring mixing, and the stirring rate is preferably 600 to 1500 r / min, and more preferably 750 to 1200 r / min.

[0059] In the present invention, the raw materials other than SEBS and white oil are pre-dispersed before mixing; the specific steps of the pre-dispersion are: pouring the raw materials other than SEBS and white oil into a high-speed mixer according to the formula ratio, mixing for 1 to 10 minutes at a stirring rate of 600 to 1000 r / min to obtain a premix.

[0060] In the present invention, the extrusion granulation is carried out in a twin-screw extruder, and the temperature of the extrusion granulation is preferably 180 to 210°C, and more preferably 190 to 200°C.

[0061] In the present invention, before the molding, the product obtained by extrusion granulation is pressed into a film; the pressing is carried out in a double-roll mill, and the pressing temperature is preferably 170-190°C, more preferably 180°C; the thickness of the film is preferably 0.2-2mm, more preferably 0.5-1mm.

[0062] In the present invention, the molding is performed in a tablet press or an injection molding machine, and the molding is preferably static compression molding or injection molding.

[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] Preparation of microcapsule phase change energy storage magnesium salt:

[0066] 1 mol of sodium dodecylbenzene sulfonate is placed in water to obtain an aqueous solution of sodium dodecylbenzene sulfonate with a mass concentration of 1 wt%; paraffin is heated at 55°C to a clear liquid state, and then the aqueous solution of sodium dodecylbenzene sulfonate is added dropwise to the paraffin solution at a rate of 0.025 mL / s (the molar number of the paraffin solution is controlled to be 1 mol) to obtain a milky white emulsion, which is stirred at a rate of 500 r / min for 60 min; then 1 mol of ultrafine magnesium hydroxide with a median particle size of 0.9 μm is added to the emulsion, mechanically stirred at 50°C, the stirring rate is controlled to be 1000 r / min, and after stirring for 24 hours, a magnesium hydroxide emulsion colloid is obtained; then centrifuged at 4500 r / min for 25 minutes, and washed with water 3 times; finally, the washed product is dispersed in water, the amount of water is controlled to be 5 wt% of the mass of the washed product, and freeze-dried at -35°C for 14 hours to obtain a microcapsule phase change energy storage magnesium salt.

[0067] Preparation of SEBS composite materials:

[0068] The raw materials and amounts used are as follows: 30 parts of KRATON SEBSG-1654, 10 parts of polypropylene PPH-T-022, 30 parts of the microcapsule phase change energy storage magnesium salt obtained above, 5 parts of dioctyl phthalate, 1 part of a composite anti-aging agent of phosphite and hindered phenol antioxidant 1010 in a mass ratio of 1:1, 1 part of a composite lubricant of zinc stearate and calcium stearate in a mass ratio of 1:1, 5 parts of acrylonitrile-butadiene-styrene copolymer, and 10 parts of 26# white oil.

[0069] Preparation steps: KRATON SEBS G-1654 and 26# white oil are stirred and mixed at a rate of 1000 r / min to obtain a mixture; the remaining raw materials are mixed at a rate of 600 r / min for 5 minutes for pre-dispersion, added to the mixture, mixed, and extruded into granules using a twin-screw extruder at 180° C., and then the granules obtained by granulation are added to a double-roll open mill and pressed into a film at a temperature of 180° C., the thickness of the film is maintained at 1 mm, and the film is pressed on a small tablet press by static molding to obtain a SEBS composite material.

[0070] The SEBS composite material obtained in this embodiment was tested, and the test results are as follows: Figure 1 and 2 As shown. Figure 1 It can be seen that the microcapsule phase-change energy storage magnesium salt obtained in this example has a typical core-shell structure, has a good encapsulation effect, and has a moderate thickness ratio between the core and the wall material. Figure 2It can be seen that the particle size distribution of the microcapsule phase-change energy storage magnesium salt obtained in this embodiment is mainly concentrated in 5-6 μm, the distribution is relatively uniform, and the overall microencapsulation effect is good.

[0071] Example 2

[0072] Preparation of microcapsule phase change energy storage magnesium salt:

[0073] 0.05 mol of hexadecyltrimethylammonium bromide is placed in water to obtain an aqueous solution of hexadecyltrimethylammonium bromide with a mass concentration of 0.1 wt%; paraffin is heated at 30°C to a clear liquid state, and then the aqueous solution of hexadecyltrimethylammonium bromide is added dropwise to the above paraffin solution at a rate of 0.05 mL / s (the molar number of the paraffin solution is controlled to be 0.5 mol) to obtain a milky white emulsion, which is stirred for 120 min at a rate of 100 r / min; then 1 mol of ultrafine magnesium hydroxide with a median particle size of 1 μm is added to the above emulsion, mechanically stirred at 30°C, the stirring rate is controlled to be 100 r / min, and after stirring for 48 hours, a magnesium hydroxide emulsion colloid is obtained; then centrifuged at 1000 r / min for 80 minutes, and washed with water 3 times; finally, the washed product is dispersed in water, the amount of water used is controlled to be 1 wt% of the mass of the washed product, and freeze-dried at -10°C for 48 hours to obtain a microcapsule phase change energy storage magnesium salt.

[0074] Preparation of SEBS composite materials:

[0075] The raw materials and amounts used are as follows: 20 parts of KRATON SEBSG-1654, 15 parts of polypropylene PPH-T-022, 5 parts of the microcapsule phase change energy storage magnesium salt obtained above, 4 parts of dioctyl phthalate, 1 part of a composite anti-aging agent of phosphite and hindered phenol antioxidant 1010 in a mass ratio of 1:1, 1 part of a composite lubricant of zinc stearate and calcium stearate in a mass ratio of 1:1, 2 parts of acrylonitrile-butadiene-styrene copolymer, and 2 parts of 500N white oil.

[0076] Preparation steps: KRATON SEBS G-1654 and 500N white oil are stirred and mixed at a rate of 600 r / min to obtain a mixture; the remaining raw materials are mixed at a rate of 800 r / min for 5 minutes for pre-dispersion, added to the mixture, mixed, and then extruded and granulated at 190° C. using a twin-screw extruder, and then the granulated pellets are added to a double-roll mill and pressed into a film at a temperature of 180° C., and the thickness of the film is preferably maintained at 1.5 mm, and injection molding is performed by an injection molding machine to obtain a SEBS composite material.

[0077] Example 3

[0078] Preparation of microcapsule phase change energy storage magnesium salt:

[0079] 10 mol of sodium didodecylphenyl ether disulfonate is placed in water to obtain an aqueous solution of sodium didodecylphenyl ether disulfonate with a mass concentration of 10 wt%; paraffin is heated at 80°C to a clear liquid state, and then the aqueous solution of sodium didodecylphenyl ether disulfonate is added dropwise to the paraffin solution at a rate of 0.005 mL / s (the molar number of the paraffin solution is controlled to be 5 mol) to obtain a milky white emulsion, which is stirred for 10 min at a rate of 1000 r / min; then 1 mol of ultrafine magnesium hydroxide with a median particle size of 1.2 μm is added to the emulsion, mechanically stirred at 90°C, the stirring rate is controlled to be 2000 r / min, and after stirring for 1 h, a magnesium hydroxide emulsion colloid is obtained; then centrifuged at 9000 r / min for 5 min, and washed with water 3 times; finally, the washed product is dispersed in water, the amount of water used is controlled to be 10 wt% of the mass of the washed product, and freeze-dried at -80°C for 1 h to obtain a microcapsule phase change energy storage magnesium salt.

[0080] Preparation of SEBS composite materials:

[0081] The raw materials and amounts used are as follows: 40 parts of KRATON SEBSG-1654, 1 part of polypropylene PPH-T-022, 40 parts of the microcapsule phase change energy storage magnesium salt obtained above, 8 parts of dioctyl phthalate, 1 part of a composite anti-aging agent of phosphite and hindered phenol antioxidant 1010 in a mass ratio of 1:1, 1 part of a composite lubricant of zinc stearate and calcium stearate in a mass ratio of 1:1, 8 parts of acrylonitrile-butadiene-styrene copolymer, and 12 parts of 46# white oil.

[0082] Preparation steps: KRATON SEBS G-1654 and 46# white oil are stirred and mixed at a rate of 1500r / min to obtain a mixture; the remaining raw materials are mixed at a rate of 900r / min for 5 minutes for pre-dispersion, added to the mixture, mixed, and extruded into granules using a twin-screw extruder at 200°C, and then the granules obtained by granulation are added to a double-roll open mill and pressed into a film at a temperature of 180°C, and the thickness of the film is preferably maintained at 1.8mm, and the film is pressed on a small tablet press by static molding to obtain a SEBS composite material.

[0083] Comparative Example 1

[0084] The difference from Example 1 is that the molar number of the paraffin solution is 0.05 mol, and the rest is the same as Example 1.

[0085] Comparative Example 2

[0086] The difference from Example 1 is that the molar number of the paraffin solution is 6 mol, and the rest is the same as Example 1.

[0087] Thermal analysis and encapsulation efficiency test were performed on the microcapsule phase-change energy storage magnesium salt obtained in Examples 1 to 3 and Comparative Examples 1 to 2. The test method and test results are as follows.

[0088] Test method:

[0089] (1) Thermal analysis: The latent heat of phase change of the microencapsulated samples was measured using a TAQ20 power-compensated differential scanning calorimeter (DSC) at a heating and cooling rate of 10 °C / min and a N2 purge rate of 50 mL / min.

[0090] (2) Encapsulation efficiency: The test is performed according to the following formula: E% = (ΔH1 / ΔH2) × 100%; wherein ΔH1 is the melting enthalpy of the microencapsulated phase change energy storage magnesium salt powder, in J / g; ΔH2 is the melting enthalpy of the flexible phase change material, in J / g.

[0091] Table 1 Phase change characteristic parameters of microcapsule phase change energy storage magnesium salt obtained in Examples 1 to 3 and Comparative Examples 1 to 2

[0092]

[0093] As shown in Table 1, when the molar ratio of the flexible phase change material core and the ultrafine magnesium hydroxide wall material is in the range of 0.5 to 5:1, the enthalpy value of the microcapsule phase change energy storage magnesium salt during the melting process is relatively high, and the final encapsulation rate can also maintain a high level, especially when the molar ratio of the core and the wall material is 1:1, its melting enthalpy reaches a maximum value, and the final encapsulation rate is also the highest. However, when the ratio of the core and the wall material further increases and exceeds 5:1, the melting enthalpy of the microcapsule phase change energy storage magnesium salt decreases from 122.45 J / g to 78.65 J / g, and the encapsulation rate decreases from 49.4% to 31.8%. This is because too much core material leads to an excessively large specific surface area of ​​the core material, and the wall material is insufficient to cover the surface of the core material, so that part of the flexible phase change material cannot be coated. In addition, when the molar ratio of the core material to the wall material is in the range of 0.5 to 5:1, it shows an upward trend with the increase of the core material, and the corresponding melting enthalpy and encapsulation rate of the microencapsulated phase change energy storage magnesium salt are significantly improved. However, when the core content ratio of the flexible phase change material is too low, the proportion of the internal core material is too low, which is not conducive to the increase of the melting enthalpy and also has a certain impact on the encapsulation rate.

[0094] The thermal conductivity, flame retardancy and mechanical properties of the SEBS composite materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were tested, and the test methods and test results are as follows.

[0095] Test method:

[0096] (1) Thermal conductivity: The thermal conductivity of each test sample was tested according to the ISO22007-1-2009 thermal conductivity and thermal diffusivity test standard;

[0097] (2) Flame retardant performance: tested in accordance with UL942014 standard;

[0098] (3) The test was carried out in accordance with GB / T1040-2018 standard, with a tensile rate of 50 mm / min.

[0099] Table 2 Performance test results of SEBS composite materials obtained from Examples 1 to 3 and Comparative Examples 1 to 2

[0100]

[0101] It can be seen from the test results of Examples 1 to 3 in Table 2 that when the microcapsule phase-change energy storage magnesium salt obtained by the present invention is used in an appropriate amount, the thermal conductivity of the SEBS composite material is significantly improved, which mainly depends on the mutual phonon diffusion between the thermally conductive fillers, and as the amount of the microcapsule phase-change energy storage magnesium salt in the SEBS composite material increases, the microcapsule phase-change energy storage magnesium salt is in continuous contact with other materials, which can improve the thermal conductivity. At the same time, since the ultrafine magnesium hydroxide itself is a good inorganic, halogen-free, environmentally friendly flame retardant, it can ensure that the SEBS composite material has excellent flame retardant properties; when the amount of the microcapsule phase-change energy storage magnesium salt is reduced, the microcapsule phase-change energy storage magnesium salt is not well dispersed in the SEBS composite material, the heat conduction path is blocked, and finally the thermal conductivity of the SEBS composite material is low, and the flame retardant performance is also affected to a certain extent; when the amount of the microcapsule phase-change energy storage magnesium salt is increased, the proportion of the core material and the wall material in the microcapsule phase-change energy storage magnesium salt is large, which is reflected in the decrease in its encapsulation rate, and the thermal conductivity of the SEBS composite material is also low. Moreover, the performance of SEBS composite materials is also affected by the synergistic properties of each raw material. If the amount of emulsifier added is low, the emulsification effect of the microcapsule phase change energy storage magnesium salt is poor, and its dispersibility in the matrix is ​​also affected to a certain extent, which will also affect the mechanical properties of the SEBS composite material.

[0102] It can be seen from the test results of Comparative Examples 1 to 2 in Table 2 that when the molar ratio of the core to the wall material in the added microcapsule phase change energy storage magnesium salt is too small, the encapsulation rate is low, and it is difficult to form a good core-shell structure functional particle, which ultimately causes the thermal conductivity of the SEBS composite material to be affected to a certain extent. In addition, due to the poor dispersibility of the microcapsule phase change energy storage magnesium salt in the matrix, the flame retardant properties of the SEBS composite material are also poor, and it is difficult to pass the V-0 grade test, and it also has an adverse effect on the mechanical properties of the matrix material; when the molar ratio of the core to the wall material in the added microcapsule phase change energy storage magnesium salt is too large, the internal flexible phase change material may be difficult to be completely encapsulated in the ultrafine magnesium hydroxide wall material, and the core may be dispersed in the matrix during the processing. The dispersion effect of the microcapsule phase change energy storage magnesium salt in the matrix is ​​affected, and since the flexible phase change material is usually combustible or even flammable, exposure to the matrix reduces the flame retardant properties of the matrix material, which also has a great impact on the mechanical properties of the final SEBS composite material.

[0103] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing microcapsule phase-change energy storage magnesium salt, characterized in that: The steps include: The emulsifier, ultrafine magnesium hydroxide and flexible phase change material are mixed and reacted, and then post-processed to obtain microcapsule phase change energy storage magnesium salt; The emulsifier is an aqueous solution of one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, trimethoxysilane, tetraethyl orthosilicate, sodium oleate, sodium rosinate, sodium laurate, sodium cyclohexane, sodium didodecylphenyl ether disulfonate, sodium dibutylnaphthalene sulfonate, sodium methylene diisopropylnaphthalene sulfonate, potassium methylene diisopropylnaphthalene sulfonate and lignin sulfonate; The flexible phase change material is paraffin; The molar ratio of the flexible phase change material to the ultrafine magnesium hydroxide is 1 to 5:1; The molar ratio of the emulsifier to the ultrafine magnesium hydroxide is 0.05-10:

1.

2. The method for preparing the microcapsule phase-change energy storage magnesium salt according to claim 1, characterized in that: The mass concentration of the emulsifier is 0.1-10wt%.

3. The method for preparing microcapsule phase-change energy storage magnesium salt according to claim 2, characterized in that: The median particle size of the ultrafine magnesium hydroxide is 0.9-1.5 μm.

4. The method for preparing the microcapsule phase-change energy storage magnesium salt according to any one of claims 1 to 3, characterized in that: The temperature of the mixed reaction is 30-90° C., and the time of the mixed reaction is 1-48 hours.

5. The method for preparing microcapsule phase-change energy storage magnesium salt according to claim 4, characterized in that: The mixing reaction is carried out under stirring conditions, and the stirring rate is 100-2000 r / min.

6. The method for preparing the microcapsule phase-change energy storage magnesium salt according to claim 1 or 5, characterized in that: The specific steps of mixing the emulsifier, ultrafine magnesium hydroxide and the flexible phase change material are: mixing the emulsifier and the flexible phase change material, and then adding the ultrafine magnesium hydroxide for mixing reaction.

7. The method for preparing microcapsule phase-change energy storage magnesium salt according to claim 6, characterized in that: The mixing is stirring mixing, the mixing time is 10-120 min, the mixing temperature is 30-80° C., and the stirring rate of the mixing is 100-1000 r / min.

8. The method for preparing the microcapsule phase-change energy storage magnesium salt according to claim 1 or 5, characterized in that: The post-treatment is to centrifuge, wash and freeze-dry the product obtained from the mixed reaction in sequence; the centrifugal speed is 1000~9000r / min, and the centrifugal time is 5~80min; the reagent used for washing is water, and the number of washings is 2~3 times; the freeze-drying temperature is -80~-10℃, and the freeze-drying time is 1~48h.

9. The microcapsule phase-change energy storage magnesium salt prepared by the method for preparing the microcapsule phase-change energy storage magnesium salt according to any one of claims 1 to 8.

10. Application of the microcapsule phase-change energy storage magnesium salt according to claim 9 in SEBS composite materials for general energy thermal management devices.

Citation Information

Patent Citations

  • Preparation method of microencapsulated zirconium phosphate and halogen-free flame-retardant PC (polycarbonate) comprising microencapsulated zirconium phosphate

    CN105524301A

  • Double-layer phase-change microcapsules and production method and application thereof

    CN109852350A